The Structure and Dynamics of Hydrated and Hydroxylated Magnesium Oxide Nanoparticles - Spagnoli, Dino; Allen, J.; Parker, S. (American Chemical Society, 2011)
An understanding of the structure of water on metal oxide nanoparticles is important due to its involvement in a number of surface processes, such as in the modification of transport near surfaces and the resulting impact on crystal growth and dissolution. However, as direct experimental measurements probing the metal oxide-water interface of nanoparticles are not easily performed, we use atomistic simulations using experimentally derived potential parameters to determine the structure and dynamics of the interface between magnesium oxide nanoparticles and water. We use a simple strategy to generate mineral nanoparticles, which can be applied to any shape, size, or composition. Molecular dynamics simulations were then used to examine the structure of water around the nanoparticles, and highly ordered layers of water were found at the interface. The structure of water is strongly influenced by the crystal structure and morphology of the mineral and the extent of hydroxylation of the surface. Comparison of the structure and dynamics of water around the nanoparticles with their two-dimensional flat surface counterparts revealed that the size, shape, and surface composition also affects properties such as water residence times and coordination number.